2011
DOI: 10.1007/s12064-011-0124-1
|View full text |Cite
|
Sign up to set email alerts
|

ERG signal analysis using wavelet transform

Abstract: The wavelet analysis is a powerful tool for analyzing and detecting features of signals characterized by time-dependent statistical properties, as biomedical signals. The identification and the analysis of the components of these signals in the time-frequency domain, give meaningful information about the physiological mechanisms that govern them. This article presents the results of the wavelet analysis applied to the a-wave component of the human electroretinogram. In order to deepen and improve our knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
2
13
0
2
Order By: Relevance
“…Differently from other mother wavelets (Haar, Morlet, Daubechies), whose shapes are not similar to our traces, the MHW gives results in good agreement with the preliminary FA and for normal subjects has provided a good detection and localization of the characteristic features of the signal in regions of stationary activity that correspond either to minima or to maxima [38,39]. There exist different methods of displaying the results: we, here, calculate the absolute value of WT(s, s) coefficients and then normalize it to its maximum value for each trace [45e47]: WT abs ðs; sÞ ¼ absðWTðs; sÞÞ max½absðWTðs; sÞÞ 3The relevant frequencies are identified through the existence of clusters in the corresponding colour scalograms, that show the correlations among MHW and signal.…”
Section: Wavelet Analysis (Wa)supporting
confidence: 73%
See 2 more Smart Citations
“…Differently from other mother wavelets (Haar, Morlet, Daubechies), whose shapes are not similar to our traces, the MHW gives results in good agreement with the preliminary FA and for normal subjects has provided a good detection and localization of the characteristic features of the signal in regions of stationary activity that correspond either to minima or to maxima [38,39]. There exist different methods of displaying the results: we, here, calculate the absolute value of WT(s, s) coefficients and then normalize it to its maximum value for each trace [45e47]: WT abs ðs; sÞ ¼ absðWTðs; sÞÞ max½absðWTðs; sÞÞ 3The relevant frequencies are identified through the existence of clusters in the corresponding colour scalograms, that show the correlations among MHW and signal.…”
Section: Wavelet Analysis (Wa)supporting
confidence: 73%
“…Each scalogram yields a dominant maximum (white cluster) f 0 and one or two local maxima, f 1 and f 2 . The analysis of the clusters in the scalograms shows that it is possible to individuate in normal subjects three stable frequency components, related to the activity of the photoreceptors, whereas the values and/or the number of these frequencies are indicative of an eventual pathology [38,39,49].…”
Section: Fourier Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This study also showed that the energy level, the frequency and the latency of the two OP frequency bands had distinct luminanceresponse (LR) functions, suggesting that they might be evoked by different retinal elements/mechanisms. The CWT also revealed that the scotopic a-wave of normal human subjects was composed of three frequency components (20,140,and 180 Hz) and that the higher frequency component was absent in achromates, suggesting that the CWT could also help in the diagnosis of photoreceptoral diseases (Barraco, Persano Adorno, & Brai, 2011). Moreover, DWT coefficients were shown to be superior to traditional TD measures in segregating normal and pathological PERG waveforms using principal components analysis (Rogala & Brykalski, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…A series of work followed by Barraco et al shows the three-frequency range of occurrence between 20 and 200 Hz [1] and also analyzed the time-frequency characteristics of the a -wave in congenital stationary night blindness (CSNB) patients [2, 6]. Study on the basis of principal component analysis and wavelet analysis was used to visualise the time domain features and wavelet features (Rogala and Brykalski) [7].…”
Section: Introductionmentioning
confidence: 99%